Semiconductor Spintronics. - Xia, Jianbai, 1939- (World Scientific, 2012)
Semiconductor Spintronics, as an emerging research discipline and an important advanced field in physics, has developed quickly and obtained fruitful results in recent decades. This volume is the first monograph summarizing the physical foundation and the experimental results obtained in this field. With the culmination of the authors' extensive working experiences, this book presents the developing history of semiconductor spintronics, its basic concepts and theories, experimental results, and the prospected future development. This unique book intends to provide a systematic and modern found.